Nanoscaled Films and Layers - Nanai, Laszlo (IntechOpen, 2017)
In recent years, scientific investigations and technological developments have resulted in many new results. Direct applications of quantum mechanical laws to system with length scales lower than 100 nm (nano) had opened a way to construction of new equipment in the field f.e. of nano- and optoelectronics. This book fits into this trend summarizing the results related to discoveries and technological applications of nanolayer in different fields of material science and even life science. The chapters are organized into three subfields: -Preparation and fabrications of nanolayers with different methods. -Description of recent achievements related to very important III-V heterostructures. -Descriptions of mechanical, thermal, optoelectronic, photocatalytic, and tribological properties of nanolayered structures. Some environmentally friendly applications are also treated in this book. The presented book provides a description of specific and original results obtained by authors. We hope that the volume will be of interest for a wide range of readers working in the field of material science.